2006
DOI: 10.1073/pnas.0600236103
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary neurotrophic factor (CNTF) for human retinal degeneration: Phase I trial of CNTF delivered by encapsulated cell intraocular implants

Abstract: Neurotrophic factors are agents with a promising ability to retard progression of neurodegenerative diseases and are effective in slowing photoreceptor degeneration in animal models of retinitis pigmentosa. Here we report a human clinical trial of a neurotrophic factor for retinal neurodegeneration. In this Phase I safety trial, human ciliary neurotrophic factor (CNTF) was delivered by cells transfected with the human CNTF gene and sequestered within capsules that were surgically implanted into the vitreous of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
341
1
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 533 publications
(354 citation statements)
references
References 40 publications
5
341
1
7
Order By: Relevance
“…They were only observed when CNTF was injected before the canine retina had reached full maturation. Therefore, although this may not be an issue for adult human patients treated with sustained release of CNTF (Sieving et al, 2006), peripheral retinal changes observed in normal adult rabbits (Bush et al, 2004), and the suggestion that endogenous secretion of CNTF may be the cause of cell proliferation in humans with mutations in the NR2E3 gene (Jacobson et al, 2004) warrants further investigation. Schematic of a retinal section showing the location of the sites S1, S2, and S3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were only observed when CNTF was injected before the canine retina had reached full maturation. Therefore, although this may not be an issue for adult human patients treated with sustained release of CNTF (Sieving et al, 2006), peripheral retinal changes observed in normal adult rabbits (Bush et al, 2004), and the suggestion that endogenous secretion of CNTF may be the cause of cell proliferation in humans with mutations in the NR2E3 gene (Jacobson et al, 2004) warrants further investigation. Schematic of a retinal section showing the location of the sites S1, S2, and S3.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the inability for CNTF to cross the blood-retina barrier following systemic administration, the necessity for sustained bioavailablity of the agent in the eye, and the ocular side-effects associated with bolus intravitreal injection, a longterm intraocular delivery system has been developed (Thanos et al, 2004). This encapsulated cell-based technology (ECT) allows for the continuous release of small quantities of CNTF into the vitreous, and was evaluated in experimental animal models (Tao et al, 2002;Bush et al, 2004), and more recently in Phase I clinical trial in humans (Sieving et al, 2006). Previous work has shown that CNTF delivered through intravitreal injections (Pearce-Kelling, unpublished study), or by means of an ECT device (Tao et al, 2002), rescues photoreceptors in the rcd1 dog, an early and rapidly progressing large animal model of RP caused by a stop mutation in PDE6B.…”
Section: Introductionmentioning
confidence: 99%
“…A second approach is to slow the degeneration of photoreceptors and thus slow progression of the disease. [13][14][15][16][17][18] Finally, there are a number of approaches that do not interfere with the intrinsic progression of disease but attempt to restore photosensitivity by creating new photosensors and coupling them to the remaining retinal circuitry. Patients who are legally blind are the key target population of these therapies.…”
Section: Potential Therapies For Retinitis Pigmentosamentioning
confidence: 99%
“…1,2 It has been tested in clinical trials for Huntington's disease, 3 amyotrophic lateral sclerosis, 4 and diseases of the retina. 5 However, the mechanisms involved in CNTF neuroprotection remain largely uncharacterized.…”
Section: Introductionmentioning
confidence: 99%